Development of Kaplan Fixed Pitch Microhydro Turbine as a Renewable Energy Source at the TNI AD Border Post - Koko Hadi Santoso; Pradika Noviandani; Suryaman (International Journal of Quantitative Research and Modeling, 2026)
Micro hydropower plants offer a promising renewable energy solution for remote areas lacking access to electricity, particularly military border posts. This study aims to design and develop a fixed pitch Kaplan turbine for low head micro hydro applications. The turbine operates under a head of 1.8 m and a discharge of 0.006 m³/s. The research methodology includes theoretical calculations, numerical simulations using Computational Fluid Dynamics (CFD) and Finite Element Analysis (FEA), and experimental prototype testing. Key design parameters include runner diameter, blade configuration, shaft design, and transmission system. Simulation results show stable flow distribution and safe structural stress levels. Experimental results indicate a power output of 74.9 W with an efficiency of 70.7%. These findings demonstrate that the proposed turbine is suitable for low-head applications and can serve as an alternative energy source for remote military installations.